Trauma, Memory and Religion Journal for Religion, Film and Media - Natalie Fritz (Journal for Religion, Film and Media, 2018)
How can we screen trauma? This question might lead the perception of documentary films about atrocities in the 20th and 21st centuries, like S21 THE KHMER ROUGE KILLING MACHINE (Rithy Panh, CAMB/FR 2003) about Cambodia, THE LOOK OF SILENCE (Joshua Oppenheimer, ID/DK 2014) about Indonesia or DAS RADIKAL BÖSE (Stefan Ruzowitzky, AT 2013) about Nazi-Europe. A concern that may emerge as we watch films on atrocities is whether these artistic representations perhaps guide the public away from what "really happened". There certainly is a huge gap between, on the one hand, the immediate experience of the event that lies behind the interpretative screening and, on the other hand, watching the director's material while neither being a part nor ever having been part of the event. Yet often filmic representations are not intended to show what happened; instead they present case studies to be explored in the present. Often the films contain an inherent critique of genocidal violence and present humanistic perspectives on obedience. Mostly, these films underline the humanity of the victims, seeking to give names, faces and biographies so that they are much more than just numbers. What appears on the screen therefore challenges the audience with a moral question: what would you do?